2020
DOI: 10.1111/jocn.15123
|View full text |Cite
|
Sign up to set email alerts
|

Social support as predictor of anxiety and depression in cancer caregivers six months after cancer diagnosis: A longitudinal study

Abstract: Aims and Objectives To establish the predictive utility of specific social support domains for emotional well‐being in cancer caregivers, six months after their partner's cancer diagnosis. Background In cancer caregivers, social support has been consistently related to anxiety and depression. There is little information, however, about the predictive utility of specific social support domains for psychological well‐being in the first six months after a partner's cancer diagnosis. Design Longitudinal research s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
4
27
0
1
Order By: Relevance
“…In H 2 , we hypothesized that lower levels of caregiver social support would directly and negatively relate to caregiver depression and both internalizing and externalizing problems. While the findings showed that lower levels of caregiver social support were directly associated with caregiver depression and adolescent internalizing problems, caregiver social support was not directly linked to adolescent externalizing problems, which aligns with previous research (Angley et al, 2015 ; García‐Torres et al, 2020 ; Kingston, 2013 ). Previous research highlighted that the alleviation effect of social support on depression is particularly strong for individuals who have experienced major disruptions (Weiss, 1974 ), which provides further support for our findings because our sample came from families exposed to disadvantaged social and economic conditions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In H 2 , we hypothesized that lower levels of caregiver social support would directly and negatively relate to caregiver depression and both internalizing and externalizing problems. While the findings showed that lower levels of caregiver social support were directly associated with caregiver depression and adolescent internalizing problems, caregiver social support was not directly linked to adolescent externalizing problems, which aligns with previous research (Angley et al, 2015 ; García‐Torres et al, 2020 ; Kingston, 2013 ). Previous research highlighted that the alleviation effect of social support on depression is particularly strong for individuals who have experienced major disruptions (Weiss, 1974 ), which provides further support for our findings because our sample came from families exposed to disadvantaged social and economic conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Caregiver social support is a significant protective factor for promoting caregiver mental health and adolescent psychosocial outcomes after adverse experiences (Casale et al, 2015 ; Miller-Graff et al, 2017 ). Evidence suggests that access to social support networks could alleviate some aspects of caregivers’ depression by offsetting the challenges presented in their lives (Angley et al, 2015 ; García‐Torres et al, 2020 ; Kingston, 2013 ), particularly when they have experienced major disruptions, such as residential change or the death of a spouse (Weiss, 1974 ). Moran et al ( 2019 ) found that the parents living in the disadvantaged circumstance of a refugee center in Ireland relied heavily on local services for emotional and financial support to cope with their living conditions.…”
Section: Caregiver Social Support Caregiver Depression and Children’s Behavioral Healthmentioning
confidence: 99%
“…It is important to note that blanket measures, such as lockdowns, self-isolation, and social distancing, can exert further pressures on cancer caregivers. Research suggests that social support from community members can lower anxiety and depression experienced by cancer caregivers; these supports are signi cantly limited due to social distancing recommendations [21].…”
Section: Study Protocol Registration: Prospero Crd42020196301mentioning
confidence: 99%
“…For caregivers of cancer patients social support is an indispensible part of their journey. The impact of availability of social support is directly related with the stress, psychological well-being and ultimately physical health of the caregivers [17]. Some of the major social supports the caregivers need while caring their patients is: transportation, managing daily activities and psychological support by family members and peer groups.…”
Section: Support For Social Assistancementioning
confidence: 99%